Visual Scheme Monitoring of Sensors for Fault Tolerance on Wireless Body Area Networks with Cloud Service Infrastructure. (23rd April 2014) - Jeong, Young-Sik; Kim, Hyun-Woo; Park, Jong Hyuk
Abstract : A wireless body area network (WBAN) refers to a topology of miniaturized embedded systems in and on a human body using wireless communication technology. Using the WBAN, human body data is collected to be used in various areas, including basic health information collection management, improvement of athletics capabilities, and systematic management of patients. To make use of the system in such areas efficiently, a fault or abnormal symptoms monitoring system for the sensors formed in the human body is required. Since data collection from a specific athlete can be taken care of by many people, malfunction or failure of sensors can be immediately treated. However, for patients with a variety of diseases, concentrating on their individual health information takes much effort and is time consuming. Further, when one patient is taken care of, other patients might be neglected. The present paper proposes a visual monitoring system for fault tolerance (VMSFT) that can monitor patients in a WBAN while also noticing the failure of sensors immediately. VMSFT can monitor persons who form a WBAN and infer a sensor's failure through the collected data. If VMSFT is interlinked with the emergency room, it is possible to take care of the patients proactively.